Próba oceny nowych rozwiązań w zakresie karnoprawnej ochrony dziedzictwa kultury - Trzciński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the years 2017–2018, new regulations appeared in the system of criminal legal protection of cultural heritage. It seems that some of them should significantly strengthen the protection of cultural heritage, in particular the increasing of penalties for the destruction of monuments, as well as the determination that carrying out searches for monuments without appropriate permission is treated as a crime since 2018. Unfortunately, the significant dispersion of criminal laws and the lack of an appropriate chapter in the penal code which would refer to crime against cultural heritage is still a serious drawback of the functioning system.
Keywords: dziedzictwo kulturowe; przestępstwa; drobne wykroczenia; ochrona; nowe przepisy karne